INOVASI LEKSIKAL BAHASA MELAYU RIAU DIALEK RANTAU KUANTAN DI KECAMATAN KUANTAN MUDIK - Irta Pusvita; Hasnah Faizah AR; Hermandra ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study, entitled the Lexical Innovation of Riau Malay Rantau Kuantan dialect in Kuantan Mudik District. The purpose of this study were (1) to analyzed the word experience innovation lexical full language of the Malay Rantau Kuantan Dialect in Kuantan Mudik, (2) to analyzed the word experience innovation morphological language of the Malay Rantau Kuantan Dialect in Kuantan Mudik District, (3) to analyzed and described the experience innovation phonetic word Riau Malay Rantau Kuantan dialect in Kuantan Mudik District. The method used is a qualitative method that illustrates the descriptive data. Furthermore, the results of this study found internal innovative variant 169 glossed with 434 variant, with full lexical forms of innovation are 111 glossed with 296 variants, there are 24 morphological innovation glossed with 67 variants and phonetic innovations contained in 34 glossed with 71 variants.Keywords: lexical innovation, Riau Malay language, Rantau Kuantan dialect.